Implantação de aterros sanitários: Comparação de métodos de seleção de áreas - Lino, Isabels Coutinho [UNESP]; Perinotto, José Alexandre de Jesus [UNESP]; Da Silva Cerri, Leandro Eugenio [UNESP] (My University, 2008)
Historically, the incorrect waste disposal has been related to epidemics which resulted in thousand of deaths. Despite the efforts to develop sanitary disposal methods in the 19 century, even today, uncontrolled dumps are often found in undeveloped countries. These places are responsible for environment pollution and for several diseases. The process of adequate waste disposal begins with the selection of suitable landfill areas, based on environmental characteristics. The goal of this research was to compare two methods of landfill site selection: the first one developed by IG-SMA (1999), and the other by Basílio (2001). Both methods were developed and applied in the same area - region of Campinas, São Paulo State, Brazil and this fact explains the choice for them; the comparison was made by superposing maps. Despite the same geographic area, the result was very different and few areas in common were found; IG-SMA (1999) obtained more suitable areas than Basílio (2001). This has been attributed to scale, criteria and attribute differences and, as a conclusion, Basílio (2001) was considered more restrictive than IG-SMA (1999).
Landfill site selection: Comparison of methods
Keywords: Landfill; Municipal solid waste; Site selection; comparative study; developing world; landfill; nineteenth century; site selection; waste disposal; Brazil; Campinas; Sao Paulo [Brazil]; South America